Di Bawah Penjajahan: Pasang Surut Hubungan Masyarakat Muslim dan Kolonialisme di Kawasan Samudra Hindia, 1775-1945 - Garadian, Endi Aulia (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2024)
This review discusses a book that explains the condition of Muslim societies in the Indian Ocean region from 1775 to 1945. In broad terms, this book narrates the involvement of imperial powers with Muslims in the Indian Ocean region starting from the 1770s. The historical account begins with the British East India Company (EIC) seizing Cape Town and the Moluccas, which were then controlled by the Dutch through the Dutch East India Company (Vereenigde Oostindische Compagnie, VOC). It proceeds through the period when the Ottoman Empire partnered with Britain and concludes with the Japanese occupation that overthrew Western powers in Southeast Asia in the 1940s. The strength of this book lies in its extensive use of primary sources to explore the lives of Muslims in the Indian Ocean and their interactions with colonial powers.